RELATION OF NUTRITION AND SALINITY TO GROWTH IN BLACK MOLLIES - MINBATTIWALLA, M. B.; GAZDAR, G. S. (Journal of Indian Fisheries Association, 2015)
Optimum growth, impaired growth and mortality in black molly are studied in diluted sea water, sea water and also by introducing laboratorym prepared diets. Rapid acclimation in conjunction with enhanced growth capacity was attained at 2%o concentration of common salt in water, and 2%o and 5%o dilutions of sea water. 22%o protein content in the diet was found to be adequate for growth and fertility of fishes acclimated at a salinity of 2%o. Higher protein content and other nutritive elements were necessary for fishes acclimated at 5%o and 14%o. Fertility was increased in seaswater dilutions rather than in common salt water dilutions.